Health misconceptions of the college students in La Union School of Arts and Trade and their implications for health education - Ancheta, Julita O.
This paper uncovered the health misconceptions of the college students of La Union School of Arts and Trades and how informed they are of health facts which can serve as a basis for proposing a teaching guide to enrich and update (the subject matter areas and contents) of the college health education courses. The health areas where health misconconceptions are established and the implications of these health misconceptions were also determined.